Information and profit sharing between a buyer and a supplier: Theory and practice. (11th July 2017) - Li, Kai; Liu, Xin‐Yang; Jacobson, David
Abstract : This paper is about aspects of an optimal relationship between 2 firms, a supplier and a retailer, in a 2‐party supply chain. The focus is on sharing private information when demand uncertainty exists so as to better coordinate the supply chain. It draws inspiration from a real case in Ireland of a new fish‐processing company, Oceanpath, and a supermarket chain, Superquinn, in which information was shared. The argument is that sharing the retailer's information increases supply chain profit, as well as benefiting consumers. Profit sharing will be needed to guarantee that both the retailer and the supplier gain when information is shared.